2020
DOI: 10.1021/acsapm.0c00625
|View full text |Cite
|
Sign up to set email alerts
|

Access to Fluorinated Polymer Surfaces with Outstanding Mechanical Property, High Optical Transparency, and Low Surface Energy via Nonafluoro-tert-Butyl Group Introduction

Abstract: Poly­(methyl methacrylate-co-2-hydroxyethyl methacrylate) was fluorinated using nonafluoro-tert-butanol (pK a = 5.2), and the content of incorporated nonafluoro-tert-butyl (NFtB) groups was controlled by adjustment of the monomer ratio. The developed technique was very efficient, achieving an almost quantitative (>98%) conversion of polymer hydroxyl groups under mild reaction conditions. Quantum chemical calculations showed that the dipole moment of the methyl methacrylate unit (1.77 D) increased to 3.21 D upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that incorporating fluoro-containing moieties can reduce the dielectric constant and enhance hydrophobicity. ,, Note that hydrophobicity is important for electronic materials since the D k value of water is about 80 at room temperature, therefore moisture absorption of a thermoset has a negative effect on dielectric constant. Among the fluoro-containing moieties, we focus on the symmetric tetrafluorophenylene moiety that will not increase the dipole moment due to an equal distribution of polarizable C–F bonds.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that incorporating fluoro-containing moieties can reduce the dielectric constant and enhance hydrophobicity. ,, Note that hydrophobicity is important for electronic materials since the D k value of water is about 80 at room temperature, therefore moisture absorption of a thermoset has a negative effect on dielectric constant. Among the fluoro-containing moieties, we focus on the symmetric tetrafluorophenylene moiety that will not increase the dipole moment due to an equal distribution of polarizable C–F bonds.…”
Section: Introductionmentioning
confidence: 99%